ANALISIS POSITIONINGLAYANAN BCA CABANG KUTA - Amen Wirajaya; I Putu Gede Sukaatmadja; Abdullah Jawas (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2013)
The aims of this study are investigating PT Bank Central Asia, Tbk. Kuta Branch positioning to its competitor in Bali;and superiority services of PT Bank Central Asia, Tbk. Kuta Branch based on customer perception and determining the best relevant marketing strategy for PT Bank Central Asia, Tbk. Kuta Branch to counter its  competitor.  The  data  will  be  analyzed  using  statistical  method  of  Multi  Dimensional  Scaling  and Correspondence analysis. The result of this study shows that BCA Kuta has similiarities with Mandiri, it means that Mandiri is the nearest competitor of BCA Kuta. BCA is superior in waiting time of teller services, ATM services, internet banking, and mobile banking.